2019
DOI: 10.3892/etm.2019.7713
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA‑873 inhibits the proliferation and invasion of endometrial cancer cells by directly targeting hepatoma‑derived growth factor

Abstract: An accumulation of evidence has demonstrated that abnormal microRNA (miRNA or miR) expression is associated with different types of cancer, including endometrial cancer (EC). The dysregulation of miRNAs may serve important roles in the development and progression of EC by regulating multiple aggressive biological behaviors, including cell proliferation, apoptosis, metastasis and angiogenesis. An in-depth understanding of the miRNAs associated with EC initiation and progression may be crucial for identifying su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…Moreover, DDX11-AS1 could act as an endogenous sponge to repress miR-873-5p expression. miR-873-5p was demonstrated as a tumour-suppressor in kinds of malignancies, such as colon cancer [27], thyroid cancer [28], endometrial cancer [29], glioma [30], and osteosarcoma [31]. qRT-PCR further verified the increase of miR-873-5p expression in GC tumour tissues, which was in accordance with a previous research [19].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, DDX11-AS1 could act as an endogenous sponge to repress miR-873-5p expression. miR-873-5p was demonstrated as a tumour-suppressor in kinds of malignancies, such as colon cancer [27], thyroid cancer [28], endometrial cancer [29], glioma [30], and osteosarcoma [31]. qRT-PCR further verified the increase of miR-873-5p expression in GC tumour tissues, which was in accordance with a previous research [19].…”
Section: Discussionsupporting
confidence: 89%
“…As a tumour-associated miRNA, miR-873a-5p has been well recognized to regulate tumour proliferation and invasion by modulating certain molecules in colorectal cancer, endometrial cancer and hepatocellular carcinoma [24][25][26]. Cui et al reported that the expression level of miR-873a-5p in breast tumours was much lower than normal.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that HDGF is a representative member of a gene family ( Figure 1; Figure 2) might be advantageous when we consider it as a therapeutic target. Recently, the significant roles of HDGF in malignant diseases were reported for many non-digestive malignant diseases, including osteosarcoma [61,62], endometrial cancer [63,64], lung cancer [65][66][67], malignant glioma [68][69][70], cervical cancer [71], ovarian cancer [72] and breast cancer [73]. Thus, HDGF is considered as a potential target molecule for anticancer therapy.…”
Section: Hdgf As a Potential Target Molecule For Anticancer Therapymentioning
confidence: 99%